PROBLEM OF PROFESSIONAL FORMATION COMPETENCIES OF THE FUTURE SPECIALIST IN CONTEXTS OF IMPLEMENTATION OF COMPETENCE APPROACH IN HIGHER PROFESSIONAL EDUCATIONAL INSTITUTIONS OF UKRAINE (Pedagogy of Higher and Secondary Education, 2008)
This article considers the problem of formation of the professional competence of future specialists in the context of realization of the Competence-Based Approach in the higher professional school. It reveals the main points of view on its introduction and its results; it studies the structure and the main constituents of the professional competence of future specialists.